Effect of threshold on the correlation between airflow obstruction and low attenuation volume in smokers assessed by inspiratory and expiratory MDCT. (April 2015) - Yanagawa, Noriyuki; Kawata, Naoko; Matsuura, Yukiko; Sugiura, Toshihiko; Suzuki, Toshio; Kasai, Hajime; Irie, Ryosuke; Iesato, Ken; Tada, Yuji; Tanabe, Nobuhiro; Suzuki, Yoichi; Tatsumi, Koichiro
Background: The estimation of emphysematous changes is very sensitive to computed tomography (CT) threshold level. In clinical practice, the predetermined threshold is usually set at −950 Hounsfield units (HU) for the detection of low attenuation volume (LAV). However, threshold levels that are tightly connected to pulmonary function abnormalities have not been determined. Purpose: To determine the threshold level for calculating an LAV that closely reflects airflow limitation in patients with chronic obstructive pulmonary disease (COPD). Material and Methods: Seventy-six consecutive non-COPD smokers and COPD patients underwent paired inspiratory and expiratory multidetector CT (MDCT). LAV% was segmented every 10 HU between −1000 and −750 HU to examine the correlation between LAV% and indexes of obstructive impairment. Results: LAV% gradually increased as the threshold level increased on both inspiratory and expiratory images. LAV% on inspiratory images was higher than that on expiratory images at all threshold levels between −1000 and −750 HU. The threshold level that correlated with obstructive impairment differed between the two images: −930 HU on inspiratory and −870 or −880 HU on expiratory images. Conclusion: LAV% dramatically changed according to the threshold level on both inspiratory and expiratory images, indicating that LAV% is dependent on the attenuation threshold level in patients with COPD. The threshold linking LAV% to airflow limitation was higher on expiratory than on inspiratory images.